1985
DOI: 10.1111/j.1471-4159.1985.tb07112.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine, Serotonin, and Acid Metabolites in Brain Regions from the Developing Offspring of Ethanol‐Treated Rats

Abstract: Female rats were pair-fed control or ethanol liquid diets on a chronic basis prior to parturition. Six brain regions (hypothalamus, cerebellum, brain stem, cortex, corpus striatum, and hippocampus) were dissected from 19- and 35-day-old rat offspring for the determination of dopamine (DA), serotonin (5-HT), 3,4-dihydroxyphenylacetic acid (DOPAC), 5-hydroxyindoleacetic acid (5-HIAA), and homovanillic acid (HVA). DA, 5-HT, and the acid metabolites were separated simultaneously by reverse-phase HPLC and were quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…The electrical activity of DA neurons is critical in controlling the synthesis and release of DA (Gonon and Buda, 1985; SuaudChagny et al, 1992). Therefore, we suggest that prenatal ethanol exposure-induced reduction in the electrical activity of DA neurons could contribute to decreased DA function characterized in previous biochemical studies ( Rathbun and Druse, 1985;Cooper and Rudeen, 1988;Druse et al, 1990;Szot et al, 1999). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The electrical activity of DA neurons is critical in controlling the synthesis and release of DA (Gonon and Buda, 1985; SuaudChagny et al, 1992). Therefore, we suggest that prenatal ethanol exposure-induced reduction in the electrical activity of DA neurons could contribute to decreased DA function characterized in previous biochemical studies ( Rathbun and Druse, 1985;Cooper and Rudeen, 1988;Druse et al, 1990;Szot et al, 1999). …”
mentioning
confidence: 99%
“…Impaired attention (Hausknecht et al, 2005) and dysfunctions of the mesolimbic/ cortical DA system are also observed in rats with prenatal ethanol exposure. Therefore, prenatal ethanol-exposed rats are a feasible animal model to study the neural mechanism of attention problems in individuals with FASDs.The prenatal ethanol exposure-induced dysfunctions in the mesolimbic/cortical DA system include reduced DA synthesis, uptake sites, receptor binding sites, and DA metabolites in both DA neuron cell body and terminal areas (Rathbun and Druse, 1985;Cooper and Rudeen, 1988;Druse et al, 1990;Szot et al, 1999). Dopaminergic neurons also have smaller cell bodies and retarded dendritic growth in prenatal ethanol-exposed animals (Shetty et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is a reduction in DA uptake and receptor binding sites, DA content, and the DA metabolites in both the somatodendritic and terminal areas (Rathbun and Druse, 1985;Cooper and Rudeen, 1988;Druse et al, 1990) in prenatal ethanol-exposed animals. Prenatal ethanol exposure also can lead to changes in DA neuron morphology [e.g., smaller cell bodies and retarded dendritic growth in DA neurons (Shetty et al, 1993), DA receptor function (Shen et al, 1995;Wang and Shen, 2002), and DA receptor-mediated behavior (Hannigan and Randall, 1996)].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, all known chemical inducers of autism including cocaine, thalidomide, valproate, and alcohol modulate 5-HT levels in the brain (Harris et al, 1995;Kramer et al, 1994;Narita et al, 2002;Rathbun and Druse, 1985;Stromland et al, 1994;Williams et al, 2001). A high proportion of children with autism exhibit elevated blood 5-HT levels (hyperserotonemia) and specific alterations in 5-HT biosynthesis.…”
Section: Brain Stem and The Role Of Serotonin In Brain Development Anmentioning
confidence: 99%